Spatial patterns and driving forces of sand-binding shrubs in sand-blown and sand hazard regions of northern China - Dinghai Zhang; Haidi Qi; Yanli Wang; Ting Ning; Ruyun Tang; Yanchen Ye (Global Ecology and Conservation)
This study investigates four species of sand-binding shrubs in the fixed sand dunes of northern China’s sand-blown regions: Artemisia ordosica (AO), Caragana korshinskii (CK), Ceratoides latens (CL), and Oxytropis aciphylla (OA). The pair correlation function was employed under the Complete Spatial Randomness (CSR) and Heterogeneous Poisson (HP) null models to compare the spatial distribution and association of these four shrub species at scales of 0–20 m, encompassing both the overall population and different growth stages. For AO, the most widely distributed dominant species, both the overall population and populations in the reproductive stage exhibited an aggregated distribution under both CSR and HP models. In contrast, the less widely distributed subdominant species CL, CK, and OA showed aggregated distributions at small scales but tended towards random distributions at larger scales. Under the HP model, the intra- and inter-species spatial associations of AO with CL, CK, and OA were primarily characterized by positive interactions. The spatial patterns of AO are likely influenced by its reproductive strategy and high adaptability to arid environments. The subdominant species generally exhibited positive interactions at small scales, both intra- and inter-specific association; however, these associations often shifted to independence as the scale increased. The facilitation at small scales is primarily driven by the seed dispersal limitation and habitat association under high drought stress gradients, while the lack of interactions at medium and large scales might be attributed to soil moisture heterogeneity. This study elucidates the factors sustaining sand-binding shrub spatial patterns, thereby providing significant insights for future conservation efforts.